Has the Native Population of New England Been Dying Out? - Spengler, J. J. (Quarterly Journal of Economics, 1930)
Introduction, 2. — Previous discussions, 2. — Fertility rates, 7. — Lack of adequate data makes it impossible to reach precise conclusions of New England dying out, 9. — But such data as are available support the contention that the natives of New England are not maintaining their numbers, 14. — Conclusions, 18.